Política local de ciência e tecnologia para o desenvolvimento social : mapeamento das ações do Parque Tecnológico e da Prefeitura Municipal na cidade de São Carlos - Araújo, Juliana Sauer de (2015)
This work has as its theme the Politics of Science and Technology focusing on the city of São Carlos in the State of São Paulo. From a theoretical development of Science and Technology Policy in general in Brazil and locally analyze the case of San Carlos taking as its starting point the perspective of the Science and Technology for Social Development. Highlighting various information of socioeconomic and scientific-technical policy of the municipality, two objects of research, the Technology Park of San Carlos (ParqTec) and the Municipal Sustainable Development, Science and Technology, representing the Municipality, were studied in search up which elements contribute or not to social development. From this study we show that San Carlos is the technological center model because of the multiplicity of actions and institutions with innovative potential, but needs to consolidate to fulfill this role as a development model locally, and a C & T for social development.